LUMINOSITY LEVELS AND SOIL COMPOSITION INFLUENCE THE GROWTH OF IPECACUANHA - Ribeiro, Fernanda Naiara Santos; Huther, Cristina Moll; Oliveira, Julia Ramos de; Correia, Daniela Marques; Rodrigues, NatÃ¡lia Fernandes; Almeida, Ramonn Diego Barros de; Moraes, Jessica Barreto de; Silva, Mariana Pereira; Santos, CaÃssa Machado Machado Perucci Pereira dos; Pereira, Mariana de Oliveira; et al. (REVISTA DE AGRICULTURA, 2022)
Carapichea ipecacuanha is a medicinal plant that produces emetine and cephalin. It is on the list of species vulnerable to extinction. The objective was to verify how different substrate compositions and shading levels can interfere in the growth and development of ipecac seedlings. The following substrates were used: black soil (BS), black soil and BokashiÂ® (BS + B), black soil, sand and BokashiÂ® (BS + B + S) and black soil and sand (BS + S), and different shading levels (50 70 and 90 %). The parameters height, number of leaves, diameter and leaf area were analyzed. The shading levels had greater effect in the growth and development when compared to the substrate composition differentiation. Depending on the period, the plants in 50% showed better growth, however, between the months of November to January, these plants showed symptoms of excess of light and temperature.